CULTIVATING GENDER SENSITIVITY AND CRITICAL READING SKILLS USING FICTION: A CLASSROOM ACTION RESEARCH FOR THE STUDENTS OF ENGLISH DEPARTMENT - Puspitaning Winhar, Anggraeni Ayu; Sahid Nugroho, Higendika Rizky; Candraningrum, Dewi (Salasika, 2021)
The importance of Critical Reading Skill (CRS) and gender sensitivity to support every individual’s success in academic, personal, and social life has long been acknowledged. The accelerating advancement of technology makes the need for CRS & gender sensitivity more crucial. However, due to various factors, CRS development through the educational process has not been satisfactory. This research reviews current ideas and studies on the nature of CRS, gender sensitivity, the nature of fiction, and their role in developing CRS. To get ideas about how to implement using fiction to promote CRS & gender sensitivity, this study ends with the practical description of a step by step of using fiction with gender sensitivity to promote CRS through an instructional model. This study employs Classroom Action Research (CAR). Action research designs are systematic procedures used by teachers to gather qualitative data to address improvements in their educational setting, their teaching, and the learning of their students. Action research enables teachers to keep track and take account of the many aspects of their work with students through a systematic routine. This study aims to investigate gender sensitivity & the critical reading strategies employed by Indonesian English as Foreign Language (EFL) students. To achieve the aim of the study, the Stringer’s Action Research Model that is a cyclical and repetitive process of inquiry i.e. Look, Think, and Act was utilized. This study used Bloom’s taxonomy as useful reference tool to describe the ability of thinking simply for undergraduate EFL students. Indonesian EFL students are encouraged to employ critical reading strategies systematically thorough their reading process to engage in critical reading & gender sensitivity. The instruction of the critical reading strategies based on cognitive domain of Bloom’s taxonomy is also explicit and direct so that students are able to ask many organized and higher order questions. Throughout the study, students are also encouraged to believe that their reading difficulties were due to lack of strategies & gender sensitivity rather than a lack of their ability and skills.